Model Mutiliterasi Dalam Pembelajaran Aswaja di Perguruan Tinggi - Rahmat, Rahmat; Khoiriyah , Maulidatul (Universitas Islam Malang, 2023)
Ahlu Sunnah Wa Al-Jama'ah (ASWAJA) learning has become mandatory material to be conveyed to students both starting from the Madrasah Ibtidahiyah (MI) level to Islamic Higher Education (PTI). A logical reason behind the massive delivery of Aswaja material is to equip students so that students have qualified Aswaja insights and to create students and students who think, behave and behave in the corridors of Aqidah, Shari'a and Aswaja Morals. Attempts to internalize Aswaja for the nation's sons and daughters at every level of education are not unlikely to encounter problems if educators in the Aswaja field pay less attention to their teaching competencies because, today, 21st century society prefers learning that utilizes various sources to teach their students. Given the fact that modern-day learning is dynamic, the Multiliteracy learning model is considered very suitable to be used as an alternative and solution, because Multiliteracy will present a learning model that optimizes students' skills in reading, writing, speaking and the use of communication and information tools. This article is presented with a descriptive qualitative type research method and uses a literature study approach, practically examines, compares relevant theories from scientific books, journal articles, and final project work. The results of this study are that the Multiliteracy Model in Aswaja Learning is able to make students, especially students, become skilled in, 1) Reading the main Arabic-language literature related to Aswaja, 2) Writing down Aswaja's main ideas, 3) Conveying Aswaja's thoughts confidently, and 4) Able to utilize technology as a medium for Aswaja da'wah.